The Effect of Base Catalyst in the Citronellal Purification of Kaffir Lime Oil Precipitated by NaHSO3 and Na2SO3 - Dewi Hafidloh; NFN Warsito; Edi Priyo Utomo (Pusat Penelitian dan Pengembangan Perkebunan, 2017)
Citronellal is the main component in kaffir lime oil that has great potential utilization in industrial and pharmaceutical field. Citronellal purification using conventional method, such as destillation, requires lots of solven, special equipment and lots of time. Alternatively, purification method using base catalyst NaHSO3 and Na2SO3 as reagent could be more simple. This research aimed to evaluate the effect of the base catalyst used for hydrolysis in the purification process of citronella using salt reaction with NaHSO3 and Na2SO3 reagents. The experiments was conducted in the Laboratory of Organic Chemistry, Brawijaya University, Malang, from August 2015 to February 2016. The research was arranged a randomized block design with factorial treatments. The first treatments was two types of reagents, NaHSO3 and Na2SO3. The second one was the variations of base catalyst used for hydrolyzing NaHCO3, Na2CO3 and NaOH. The purity of hydrolyzed citronellal was measured by gas chromatography-mass spectrometry. The highest purity of citronella 89,29 % was obtained with the used of Na2SO3 reagent at the mole ratio 1:2, hydrolyzed by Na2CO3 (pH 10.98). Thus the method, can be recommended in purifying citronellal from kaffir lime oil.